Body and Trauma in Siri Hustvedt’s Works: Writing as a Therapy for Self-healing (Comparatismi, 2022)
We may think of trauma as an ongoing experience that fundamentally affects one’s ability to live fully the present and to integrate the traumatic experience into a coherent narrative. How does trauma literally reshapes both body and brain? How can the narration, particularly the process of writing, help a patient to heal the wound engraved in their body by the traumatic experience? What are the consequences of the inter-subjective relations? I propose an analysis of the body’s responses to trauma and its neuro-psycho-biological effects in Siri Hustvedt’s The Shaking Woman or a History of my Nerves, taking into consideration the neurocognitive effects generated by traumatic experiences, in particular the Dissociation and the Conversion Disorder, and the role of writing, conceived as an instrument of the memory, as a possible therapy for the re-acquisition of the self.
Keywords: Trauma; Writing; Therapy; Memory; Narrative; Intersubjectivity.